To regular teachers
 👍
 👎
 👁
Respond to this Question
Similar Questions

mathematics
7.3.6  Quiz: Solving MultiStep Equations Quiz Algebra Readiness (PreAlgebra) A / 7. Equations and Inequalities / 7.3. Solving MultiStep Equations can you check my answers 1. B 8 2. A 4 3. A 5a 4. D 7a11b 5. C 6x + 50 6. B 3

math
Tom is showing his work in simplifying (5.2 – 8.5) – 0.5 + 6.8. In which step did Tom make an error? Step 1:: (5.2 – 8.5) – 0.5 + 6.8 Step 2: 5.2 + (–8.5 – 0.5) + 6.8 (distributive property) Step 3: 5.2 – 9 + 6.8

chemistry step by step for me thank a lot
What is the weight of ca(oh)2 required for 10 litre of water remove temporary hardness of 100 ppm due to ca(H03)2 The answer 0.74 Thank all tutors for your help Pls show step by step for me

ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

math
Consider the sequence of steps to solve the equation: 5(x  3) = 7x 2 Step 1 ⇒ 10(x  3) = 7x Step 2 ⇒ 10x  30 = 7x Step 3 ⇒ 3x  30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

PLZZ HELP CIVIC PROJECT
Amendment Idea Template Your Name ____________________ Step 1: Describe how amendments have affected Americans' participation in government. Give specific examples from the lesson, including amendment names or numbers. Step 2:

math
Omar wanted to know if x−5 is a factor of the polynomial p(x)=x3−6x2−x+30. He applied the Factor Theorem and concluded that x−5 is a factor of p(x), as shown in the following work. Step 1: p(5)=53−6(52)−5+30 Step 2:

math
George Polya has a fourstep process for Problem Solving. What is the first step?

Math (Check 2 answers please)
1. What is the value of b in the equation b + 8 = 13? A. 5**** B. 8 C. 13 D. 21 2. The steps below show the incomplete solution to find the value of x for the equation 7x − 3x − 4 = −1 + 21: Step 1: 7x − 3x − 4 = −1 +

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

Quick math help
In which step below does a mistake first appear in simplifying the expression? 0.5(12c+6)3(c+4)+10(c5) Step 1: 6c+33(c+4)+10(c5) Step 2: 6c+33c12+10(c5) Step 3: 6c+33c12+10c50 Step 4: 7c41 Please help me!!! Thank
You can view more similar questions or ask a new question.